Psychological Distress and Health Insurance Coverage among Formerly Incarcerated Young Adults in the United States - Larrell L. Wilkinson; Saundra H. Glover; Janice C. Probst; Bo Cai; Lisa T. Wigfall (AIMS Press, 2015)
The United States incarcerates more people per capita than any other nation. Studies have consistently demonstrated higher prevalence of serious mental illness among the incarcerated. Although health care may be available to individuals while incarcerated, research is needed to understand the context of health care coverage and mental health after incarceration. The purpose of this study is to estimate the point prevalence of psychological distress (PD) among young adults with incarceration experience, while comparing the prevalence to that of young adults in the general population. Additionally, this study characterizes the relationship between incarceration experience and PD, while also examining this association given an individual's health insurance coverage status among young adults. Lastly, we examine if other individual, contextual, and behavioral factors influences the relationship between incarceration experience and PD, in addition to their health insurance coverage status. This study utilizes data from the 2008 panel of the National Longitudinal Survey of Youth 97, a population based survey dataset from the U.S. Department of Labor. Andersen's Behavioral Model of Health Services Use provided the conceptual framework for the study. The Mental Health Index 5 (MHI-5) was used to determine PD or normal mental health. Chi-square testing and multivariate logistic regression were performed to examine incarceration experience in association to PD. The sample with incarceration experience reported almost double the proportion of PD (21%) compared to those without an incarceration experience (11%). Young adults who have been incarcerated reported greater odds of PD than those with no incarceration experience (COR 2.18; 95% CI, 1.68-2.83) and the association was diminished in the presence of health insurance status and model covariates. Future health prevention and health management efforts should consider the impact of health insurance coverage status, health behaviors, and life satisfaction on mental health status among young adults with incarceration experience.